2021
DOI: 10.1007/s12144-021-01970-7
|View full text |Cite
|
Sign up to set email alerts
|

Why collaboration reduces suggestibility: The role of source-monitoring processes and retrieval strategies

Abstract: Previous research found that collaboration reduces the tendency to yield to misleading questions. Here, the aim was to determine whether this occurs because collaboration induces a conservative change in response criterion or because it promotes more efficient error-checking strategies. To this purpose, we compared the performance of collaborative and nominal triads in the Gudjonsson Suggestibility Scale. Critically, we recorded conversations during retrieval, allowing us to compute inclusive scores and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…These results are in line with other studies that have demonstrated how reasoning and focusing strategies, such as task-oriented, allow us to detect and reject misleading information [38,42].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with other studies that have demonstrated how reasoning and focusing strategies, such as task-oriented, allow us to detect and reject misleading information [38,42].…”
Section: Discussionsupporting
confidence: 92%
“…The effect of social pressure given by negative criticism also affects the Failure 2 score, which increases the levels of uncertainty that do not seem to be well managed by avoidance coping. According to Gilbert and colleagues [38], managing negative feedback requires more monitoring and self-control skills, which may not be guaranteed by avoidance and/or inactive coping strategies [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that individuals who interacted in presence and individuals who interacted via computer had comparable memory performance when communication was enriched with verbal and nonverbal cues. Results are in line with those reported in the study by Rossi-Arnaud et al (2023), according to which remembering in a virtual context exhibits the same general properties as its in-person counterpart, at least when using a videoconference setting. This is important because the technological revolution and, more recently, the COVID-19 pandemic, have forced individuals to communicate via video calls and video conferencing, enhancing physical distance.…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies (Abel & Bäuml, 2023;Ekeocha & Brennan, 2008;Guazzini et al, 2020;Hinds & Payne, 2016;Rossi-Arnaud et al, 2023) have attempted to investigate the effects of Internet and computer-mediated collaboration on memory. For example, Ekeocha and Brennan (2008) compared in-person interactions with computermediated ones, via chat.…”
Section: Collaborative Memory and Computer-mediated Collaborationmentioning
confidence: 99%